Differential effects of fish-oil and cocoa-butter based high-fat/high-sucrose diets on endocrine pancreas morphology and function in mice - Albeloushi, Shaima; Hasan, Amal; Arefanian, Hossein; Sindhu, Sardar; Al-Rashed, Fatema; Kochumon, Shihab; Abukhalaf, Nermeen; Jacob, Texy; Shenouda, Steve; Al Madhoun, Ashraf; Al-Mulla, Fahd; Ahmad, Rasheed (Frontiers in Endocrinology, 2024)
Background: A high-fat/high-sucrose diet leads to adverse metabolic changes that affect insulin sensitivity, function, and secretion. The source of fat in the diet might inhibit or increase this adverse effect. Fish oil and cocoa butter are a significant part of our diets. Yet comparisons of these commonly used fat sources with high sucrose on pancreas morphology and function are not made. This study investigated the comparative effects of a fish oil-based high-fat/high-sucrose diet (Fish-HFDS) versus a cocoa butter-based high-fat/high-sucrose diet (Cocoa-HFDS) on endocrine pancreas morphology and function in mice.Methods: C57BL/6 male mice (n=12) were randomly assigned to dietary intervention either Fish-HFDS (n=6) or Cocoa-HFDS (n=6) for 22 weeks. Intraperitoneal glucose and insulin tolerance tests (IP-GTT and IP-ITT) were performed after 20-21 weeks of dietary intervention. Plasma concentrations of c-peptide, insulin, glucagon, GLP-1, and leptin were measured by Milliplex kit. Pancreatic tissues were collected for immunohistochemistry to measure islet number and composition. Tissues were multi-labelled with antibodies against insulin and glucagon, also including expression on Pdx1-positive cells.Results: Fish-HFDS-fed mice showed significantly reduced food intake and body weight gain compared to Cocoa-HFDS-fed mice. Fish-HFDS group had lower fasting blood glucose concentration and area under the curve (AUC) for both GTT and ITT. Plasma c-peptide, insulin, glucagon, and GLP-1 concentrations were increased in the Fish-HFDS group. Interestingly, mice fed the Fish-HFDS diet displayed higher plasma leptin concentration. Histochemical analysis revealed a significant increase in endocrine pancreas β-cells and islet numbers in mice fed Fish-HFDS compared to the Cocoa-HFDS group.2 This is a provisional file, not the final typeset article Conclusion: Overall, our findings suggest that in a high-fat/high-sucrose dietary setting, the source of the fat, specifically fish oil, can ameliorate the effect of sucrose on glucose homeostasis and endocrine pancreas morphology and function.